Estudo, implementação e otimização de técnicas de controle avançado - Ganzaroli, Cleber Asmar (2022)
This work proposes the tuning, implementation, analysis and comparison of different control strategies applied to the same system. The controllers studied are: Proportional, Integral and Derivative, Nonlinear Predictive, Fuzzy Control and Sliding Mode Control. These techniques are applied to the speed control of an independently excited DC motor driven by a fully controlled three-phase rectifier. The methodology proposes the bench design, the modeling of the real system by the system identification method, the sensitivity analysis and the adjustments of the controllers parameters using an optimization process. Comparisons are made between the techniques, highlighting their characteristics and performance considering similar conditions of execution. The robustness of each control when acting on a non-linear system is investigated. All control techniques are applied in three different tests: i) step-type reference signal, without load application, ii) reference signal with amplitude variation, without load application and iii) step-type reference signal, with load application. The techniques present satisfactory performance in the execution of the proposed control, depending, therefore, on the analysis of the system to be implemented to determine the appropriate method.